The effect of organic fertilizer and formulated feed in pond culture of the freshwater prawn, Macrobrachium rosenbergii (de Man): prawn production - Maclean, Marlie H.; Ang, K.J.; Brown, Janet H.; Jauncey, K. (Wiley Blackwell, 1989)
The potential of organic fertilizer as a partial replacement for formulated feeds in pond culture of Macrobrachium rosenbergii (de Man) was assessed. Stocking densities reflected commercial semi‐intensive levels and the duration of the trial approached a complete grow‐out cycle. Mean weight and growth rate were examined in four treatments receiving varying levels of feed and manure. Heaviest prawns and fastest growth were evident in the treatment with decreased‐feed‐increased‐manure. Production assessed as marketable percentages (74.56, 52.21, 13.28 and 11.12) resulted in significantly different marketable yields of 2029, 1284, 336 and 103 kg/ha/year for decreased‐feed‐increased‐manure, feed‐plus‐manure, feed‐only, and manure‐only respectively assuming 2‐6 batch cycles per year under prevailing conditions. Total survival was significantly highest in feed‐only (72.80%), intermediate in feed‐plus‐manure (40.59%) and decreased‐feed‐increased‐manure (36.32%), and lowest in manure‐only (26.77%) treatments. Prawns were separated at harvest into four morphotypes as berried females, females without eggs, immature males and adult males. Average individual weight and group bicmass were determined for each morphotype. Only prawn production data are presented here. Analyses of water, soil and benthic fauna will be presented in future publications.